The Role of Islamic Religious Counselors in Fostering Religious Awareness in Samudera Sub-District North Aceh - Arsyi, Ahmad (Enlightenment Publishing, 2025)
In my paper, I explore the significant role of Islamic religious counselors in fostering religious awareness within the community of Samudera Sub-District, North Aceh. I begin by contextualizing religious awareness through the lens of Islamic teachings and Acehnese cultural traditions, particularly in the aftermath of socio-political conflict. I address the research question regarding the contributions of these counselors in enhancing religious understanding and practice among residents. The study examines the scope and methods utilized by counselors, including individual counseling, group discussions, and public lectures, alongside case studies that illustrate their practical applications. Furthermore, I assess the impact of these counseling efforts on religious knowledge, participation in religious activities, and overall social behavior among the community members. The research also highlights challenges faced by counselors and potential strategies for improving their effectiveness. Ultimately, this study underscores the vital importance of Islamic religious counseling as a mechanism for promoting religious awareness and social cohesion in North Aceh.